Towards a Research Agenda on Individual Differences in ELT in Nigeria - Tamunobelema, Isaac; Ahaotu, Joseph Onyema (Journal of Gender and Power, 2021)
There are a variety of individual differences that English language teaching (ELT) professionals cannot afford to ignore. This essay is based on a premise that teaching and learning English in Nigeria’s multilingual background of 526 languages (Ethnologue, 2018) present an extraordinary context of multiculturalism and individual differences in the language classroom. ELT professionals in such a context require significant expertise in the application of inclusive practices. The essay identified gaps in the praxis and policy dimensions of Nigerian ELT practice relating to individual differences and suggested a research focus on these two areas. It concluded that teachers should adopt clear, empirically tested methodologies to cater for the different students in the class, create good relationships in the classroom to develop learner self-confidence, integrate activities and tasks that clearly appeal to different learning styles and personalities, personalize learning as much as possible, create learner autonomy, and pay attention to cultural variations among L2 learners.